МОДЕЛЬ ОПТИМІЗАЦІЇ ФУНКЦІОНУВАННЯ МІКРОМЕРЕЖІ З СЕС ТА УСТАНОВКОЮ ЗБЕРІГАННЯ ЕНЕРГІЇ - Блінов, І.В.; Парус, Є.В.; Шиманюк, П.В.; Ворушило, А.О. (Інститут електродинаміки НАН України, Київ, 2024)
The article provides a description of the microgrid function optimization model for solving the problem of reducing the cost of electricity purchases by the owner of such a microgrid on the retail electricity market. The objective function of minimizing the cost of electricity purchase has been formalized. Approaches to determining the coefficients of penalty functions designed to cut off technically unacceptable modes of the microgrid have been determined. A mathematical model of an energy storage system (ESS) is proposed, in which the functions of calculating the technological costs of electricity are formalized. A system of constraints for the problem of minimization of the cost of electricity purchase is given. Approaches to solving the problem of evaluating the effect of SPP and ESS operation in microgrids using optimization results are determined. Examples of microgrid operation optimization for an enterprise with its own SPP and ESS are presented. The need for additional control of the economic expediency of involving ESS in the regulation of electricity balances at the enterprise was noted. References 17, figures 3, table 1.